Retinal ganglion cell function in recovered optic neuritis: Faster is not better. Issue 9 (September 2018) - Monsalve, Pedro; Ren, Sandy; Jiang, Hong; Wang, Jianhua; Kostic, Maja; Gordon, Philip; Porciatti, Vittorio
Highlights: Patients with Multiple Sclerosis and past history of optic neuritis (ON) can have normal clinical vision. Pattern Electroretinogram (PERG) responses, reflecting mass retinal ganglion cell responses, show shortened latency in eyes with resolved ON. Faster function, as measured by PERG, is not better, as this implies loss of smaller axons in the optic nerve. Abstract: Objective: To assess residual retinal ganglion cell (RGC) function in patients with recovered optic neuritis (ON) and multiple sclerosis (MS). Methods: Age-matched controls (C, n = 32) and MS patients ( n = 17) with history of ON in one eye but normal visual acuity and color vision were tested with steady-state Pattern Electroretinogram (PERG). Light Emitting Diodes (LED)-generated bar gratings, robust signal averaging and Fourier analysis were used to assess response amplitude and latency. Results: PERG amplitude was similar for C, ON and fellow eyes (FE) ( P = 0.4), but PERG latency was shortened in ON by 3.2 ms ( P = 0.002) and in FE by 2.0 ms ( P = 0.02) and was correlated ( P < 0.01) with both Retinal Nerve Fiber Layer (RNFL) and Ganglion Cell Inner Plexiform Layer (GCIPL) thicknesses. PERG latency shortening could be simulated in control subjects ( n = 8) by dioptrically blurring the edges of gratings (high spatial frequencies), which reduced activity of parvocellular RGCs with smaller/slower axons. The blurred PERG latency was shorter than baseline by 2.9 ms ( P = 0.01). Conclusions: PERG latency is shortened in both eyes of MS patients with recovered unilateral ON, suggesting relative dysfunction of RGCs with slower axons and sparing of RGCs with faster axons. Significance: Assessment of PERG latency in MS and ON may help identifying and monitoring RGC dysfunction. PERG latency shortening in FE suggests primary retinopathy in MS.